Pendampingan Optimalisasi Pemasaran Produk Melalui Digital Platform dan Implementasi Pelayanan Prima untuk Meningkatkan Kepuasan Pelanggan di PT Sasana Lintas Indo - Safna Kurnia Putri; M. Abrar Habibullah; Hafiz Muhammad Saad; Evan Stiawan (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article focuses on the analysis of marketing strategies for tourism products of PT Sasana Lintas Indo in Bengkulu through the framework of the 4P marketing mix theory (Product, Promotion, Price, Place). The type of research used is descriptive qualitative, utilizing primary and secondary data, as well as methods of observation, interviews, and documentation to deeply uncover how PT Sasana Lintas Indo implements marketing strategies to increase its customer base. Research findings show that PT Sasana Lintas Indo Bengkulu uses a combination of digital marketing through social media advertising and direct marketing through visits and partnerships. Furthermore, this research also highlights the implementation of excellent service as an integral part of their strategy, reflected in participation in religious gatherings, partnerships with institutions, payment flexibility, and a focus on service quality for tourists. Thus, this study not only examines marketing strategies for tourism products, but also emphasizes the importance of implementing excellent service in PT Sasana Lintas Indo's efforts to attract and retain customers.